Improvement of Condensation Model With the Presence of Non-Condensable Gas for Thermal-Hydraulic Analysis in Containment - Wang, Tianlin; Wang, Di; Tong, Lili; Cao, Xuewu (Frontiers in Energy Research, 2021)
Steam condensation plays a key role in prediction of the pressure behavior and hydrogen distribution in the containment during a hypothetical loss-of-coolant accident or a severe accident in a light water nuclear reactor. The objective of this study is to evaluate and improve the condensation model in GASFLOW code. Reynolds analogy coupled with wall function and Chilton-Colburn empirical analogy is used to model heat and mass transfer in GASFLOW, which has requirements for dimensional distance of the first cell near the wall and some deficiencies in description of heat and mass transfer process in the stagnant zone. Based on the evaluation of original condensation, the results shows good agreement with COPAIN experiment cases where the mass fraction of air ranges from 76.7 to 86.4%. However, with the changes in geometry of the facility and the presence of helium, the original model has a large deviation in the prediction of pressure, temperature and gas distribution compared with MISTRA ISP47 (OECD International Standard Problem No. 47) experiment data. This work proposes a modified condensation model which uses McAdams correlation and Schlichting correlation with a weight factor to calculate natural, forced, or mixed convection heat transfer coefficient, and adopts Chilton-Colburn empirical analogy to model mass transfer. The modified model has no requirement for the dimensionless distance near the wall in heat and mass transfer calculation and improves the prediction performance of heat transfer in stagnant zone. The prediction result of the modified model shows good agreements with MISTRA ISP47 problem, and the error of it compared with COPAIN experiment data is within 25% which is the same as that predicted by the original model.